Does Human Development Translate into Inclusive Welfare? Evidence from Regional Economic Dynamics in Indonesia - Miharsih, Anik (Journal of Regional Economics Indonesia, 2026)
The relationship between human development and inclusive welfare remains a central issue in regional development, particularly in emerging economies where improvements in the Human Development Index (HDI) do not always translate into equitable socioeconomic outcomes. This study examines the linkage between HDI-related public investment and welfare dynamics in Jombang Regency, Indonesia. Using a quantitative approach based on time-series secondary data (2010–2024), the study employs polynomial regression and correlation analysis to evaluate the effects of education spending, health spending, wages, and demographic dynamics on poverty and household consumption. The results show that health expenditure has a strong negative association with poverty reduction, while education spending exhibits a nonlinear (U-shaped) relationship, indicating potential inefficiencies in translating educational investment into welfare outcomes. In addition, wages strongly influence household food consumption, whereas population growth demonstrates a diminishing marginal effect on consumption dynamics. These findings suggest that improvements in human development must be integrated with labor market absorption and regional economic structures to generate inclusive and sustainable welfare outcomes.